2008
DOI: 10.1021/bi8009357
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Spermidine/Spermine N1-Acetyltransferase in Complex with Spermine Provides Insights into Substrate Binding and Catalysis,

Abstract: The enzyme spermidine/spermine N (1)-acetyltransferase (SSAT) catalyzes the transfer of acetyl groups from acetylcoenzyme A to spermidine and spermine, as part of a polyamine degradation pathway. This work describes the crystal structure of SSAT in complex with coenzyme A, with and without bound spermine. The complex with spermine provides a direct view of substrate binding by an SSAT and demonstrates structural plasticity near the active site of the enzyme. Associated water molecules bridge several of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…The acetylation rate of N 1 AcTETA was approximately 10% at 10 mM compared with TETA at 10 mM using the spectrophotometric method (Coleman et al, 2004) (data not shown). Furthermore, we determined the kinetic values for acetylation of TETA using hSSAT1 to compare the properties of the human and mouse recombinant enzymes that show high structural homology (Hegde et al, 2007;Montemayor and Hoffman, 2008 (Weisell et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The acetylation rate of N 1 AcTETA was approximately 10% at 10 mM compared with TETA at 10 mM using the spectrophotometric method (Coleman et al, 2004) (data not shown). Furthermore, we determined the kinetic values for acetylation of TETA using hSSAT1 to compare the properties of the human and mouse recombinant enzymes that show high structural homology (Hegde et al, 2007;Montemayor and Hoffman, 2008 (Weisell et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, there are several acetyltransferases where the guanidine side chain of an arginine is positioned within 3 Å of the 3 0 -phosphoanion of bound CoA. These include spermine-spermidine acetyltransferase (Arg 142 and Arg 143 ) [39] and serotonin acetyltransferases (Arg 170 ) [40]. Both arginine and lysine residues readily undergo post-translational modification, including methylation, acetylation sumoylation and ubiquitination, which would be a novel mechanism for regulating acetyltransferase activity by altering AcCoA binding.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of the human and mouse SSAT protein have been obtained in the presence and absence of ligands including substrates and inhibitors (Fig. 3) [15-17]. These studies provide a good understanding of the reaction mechanism and the substrate specificity.…”
Section: Ssat: a Highly Regulated Rate-limiting Step In Polyamine Camentioning
confidence: 99%